THE INTEREST OF THE WORKING IFUGAO TRIBE YOUTH RESIDING IN THE URBAN BARANGAYS IN BANAUE ON THE PRESERVATION OF THE BANAUE VIEW POINT RICE TERRACES ( March 2007) - Baylosis, Jade A.; Beltran, Sarah D.; Mendoza, Valerie Anne C.; Rosales, Elaine Catherine A. and Vasquez, Yvette G. 4 0 16; 5 (2007)
u
Thesis (Undergraduate) Pamantasan ng Lungsod ng Maynila, 2007.;Bachelor of Science in Mass Communication.
Keywords: 2 -- 0; 6; 20; 20; 2